"Nudge" in Lucca's Hospital: separate waste collection improvement and cigarettes dumping reduction. (30th September 2020) - Canale, A; Giardi, F; Gandolfo, S; Lorenzi, V; Corda, V; Farneti, S; Taddeucci, M; Maielli, M; Privitera, G; Mencaroni, S
Abstract: Background: Positive behaviour and user's collaboration improved by using choices orientation techniques; in Lucca's Hospital (North-West Tuscany Sanitary Authority) this approach has improved separate waste collection execution and has decreased cigarettes dumping in commons areas. Objectives: Phase 1 (May 2019): amendment of choices architecture recyclable waste bins in commons areas and into the wards were boosted, with "islands" clearly visible from any point of common paths; in the transit areas were installed exclusively multi-material and paper bins, equipped with signs that clearly indicate which products deliver; residual waste bins were allowed exclusively in certain points. ashtrays at the hospital entrances were eliminated and replaced with signage indicating smoking cessation benefits and the presence of areas "put your cigarette out" along the structure approach routes. Phase 2 (scheduled for May 2020): "nudge" action Spreading in community (using press and social-media) and locally (using poster) of the slogan "In San Luca we are taking a step forward: don't lag behind!". This message stimulate the perception of an ongoing change to join. Results: A decrease in residual waste collection and in instances of non-compliance in separate waste collection was detected. Decorum in the outdoor environments improved, with a reduction of user's reports and extra-cleaning interventions. Conclusions: The described actions have improved user's collaboration, management efficiency of waste disposal and cleaning service, perceived quality and cost. Key messages: Imitating a social model appears to be successful motivator of virtuous behaviours. Choices architecture and "nudge" techniques may improve citizens' care pathways governance.